Evaluation of phototherapy effects on platelet numbers and volumes in neonates with unconjugated hyperbilirubinemia in Sulaimani city/Kurdistan region/Iraq - Hayder Fakhir Mohammad; Shano Yassin Abdulqadir; Dea Ali Abdulla; Hawnaz Muhamad Ibrahim (Iraqi Journal of Hematology)
BACKGROUND: Unconjugated hyperbilirubinemia is a rather common disease that affects 60% of term and 80% of preterm infants within their 1st week of life. Phototherapy is considered the safest method for the treatment of unconjugated hyperbilirubinemia in neonates, which is the most common problem in the neonatal period. OBJECTIVES: To identify the effect of phototherapy on platelet numbers and volumes, and if the duration of treatment, gestational age, birth weight and other factors have some influences on this effect. PATIENTS, MATERIALS AND METHODS: A prospective cohort study was conducted from November 1, 2023, to April 1, 2024. Seventy-four neonates were enrolled in this study including males and females (1.39:1), with different gestational ages and birth weights. Neonates were selected according to the specific inclusion and exclusion criteria. Thorough history and physical examination performed with several laboratory investigations sent. Total serum bilirubin measured before starting phototherapy, after 24 hours, 48 h, 72 hours, and 4 days later. SPSS program was used to code, enter, and process the gathered data. RESULTS: Platelet number in general decreased with increasing duration of phototherapy regardless of other parameters (P = 0.045). In correlation to the duration of phototherapy and time of jaundice appearance, it was statistically significant for only neonates who required phototherapy for more than 4 days and time of jaundice appearance between 1 and 3 days (P = 0.042). Platelets number decreased with increasing duration of phototherapy especially in low birth weight and very low birth weight neonates, P value 0.028 and 0.047 respectively. There were statistically significant values (P = 0.002 and P = 0.001) in the correlation of decreasing platelet numbers to gestational age and duration of phototherapy, especially more evident with gestational age below 37 weeks (preterm) and in periods after 24 h and 72 h. There were no statistically significant values in platelet volumes in correlation to any of the previous parameters. CONCLUSIONS: Platelets number decreased with phototherapy management, and it is more evident with longer phototherapy duration, low birth weight and early onset, while platelet volume not affected. Hence, it is recommended to avoid unnecessary prolongation of phototherapy.